(untitled) (Sebha University Conference Proceedings, 2025)
The current research aimed to shed light on the creative teaching skills of the university professor and and its practical applications, as one of the modern methods of development and success of the university in general, and teaching is one of the main tasks of the university professor, as the process of acquiring teaching skills in a modern and effective manner varies from one professor to another, The current research aimed to shed light on the creative teaching skills of the university professor and the criteria for their application, as one of the modern methods of development and success of the university in general, and teaching is one of the main tasks of the university professor, as the process of acquiring teaching skills in a modern and effective manner varies from one professor to another.